2010
DOI: 10.1007/s00418-010-0728-4
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of YAP1 induces immortalization of normal human keratinocytes by blocking clonal evolution

Abstract: YAP1 is a transcriptional co-activator able to bind several transcription factors. YAP1 was termed a candidate oncogene after it was shown to be in human chromosome 11q22 amplicon; besides the genomic amplification, several experiments indicated that it has oncogenic function. However, YAP1 was also reported to be a tumor suppressor as its gene locus is deleted in some breast cancers. To clarify the role of this protein in the physiology of rapidly renewal cells, we investigated YAP1 in human keratinocytes. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…D’Addario et al . 35 found that overexpression of YAP in normal human primary keratinocytes interfered with their normal differentiation process and led to immortalized proliferation, upregulation of the epithelial proliferation markers p63 and PCNA, and downregulation of the differentiation markers 14-3-3σ and LEKTI. In HaCaT cells, an immortalized epidermal keratinocyte cell line widely used as a cell model of psoriasis 15 18 , we found a high level of YAP that almost reached the level of YAP in the cSCC cell line A431 and was significantly higher than that in primary keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…D’Addario et al . 35 found that overexpression of YAP in normal human primary keratinocytes interfered with their normal differentiation process and led to immortalized proliferation, upregulation of the epithelial proliferation markers p63 and PCNA, and downregulation of the differentiation markers 14-3-3σ and LEKTI. In HaCaT cells, an immortalized epidermal keratinocyte cell line widely used as a cell model of psoriasis 15 18 , we found a high level of YAP that almost reached the level of YAP in the cSCC cell line A431 and was significantly higher than that in primary keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of YAP1 mediated by the LATS (large tumor suppressor) kinase, a downstream effector of the Hippo pathway, inhibits the YAP1 transcriptional activity through cytosolic sequestration and is involved in cell contact inhibition. Furthermore, recent reports demonstrate the crucial function of YAP1 in the control of epidermal proliferation (47, 48). Interestingly, our results clearly establish down‐regulation of YAP1 by miR‐483‐3p as a new regulatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Yes-associated protein 1 (YAP), a major downstream effector of the Hippo pathway, is phosphorylated and inactivated by the serine/threonine kinases large tumor suppressor 1 (LATS1) and LATS2 [102, 103]. YAP dephosphorylation is associated with the senescence of rat nucleus pulposus cells and overexpression of YAP in primary human keratinocytes blocks clonal evolution and induces cell immortalization [104, 105]. Coordination of the Hippo pathway and p53 occurs in response to various types of stress signals including replication and oncogenic Ras.…”
Section: Signaling Pathways Involved In Cellular Senescencementioning
confidence: 99%